THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, CAPITAL STRUCTURE, AND STOCK PRICE ON FIRM VALUE: (Empirical Study on Banking Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2017-2021) - Indah Majidah; Desi Jelanti (Transpublika Publisher, 2023)
Corporate social responsibility (CSR), capital structure, and stock prices have garnered significant attention due to their potential impact on a firm's overall value. Corporate social responsibility involves a company's commitment to ethical and sustainable practices, extending beyond profit generation to encompass social and environmental considerations. On the other hand, capital structure reflects a company's financing composition, encompassing the balance between debt and equity. Stock prices reflect the market's perception of a company's worth and performance. This research aimed to analyze the influence of corporate social responsibility, capital structure, and stock prices on firm value within the banking sub-sector companies during the period 2017-2021. The study utilized panel data regression as its analytical technique. The sample was selected using purposive sampling from secondary data, specifically financial reports. The analysis included 33 companies observed over a 5-year period, resulting in a total of 165 data points for the investigation. Hypothesis testing was conducted using the Eviews series 9 application. The findings from the tests indicated a statistically significant simultaneous impact of corporate social responsibility, capital structure, and stock prices on firm value. However, the research revealed that corporate social responsibility, when assessed independently, did not exhibit a statistically significant impact on firm value. Conversely, the analyses demonstrated that both capital structure and stock prices had a statistically significant partial effect on firm value.